Strategi Penguatan Dakwah Islam dalam Ruang Digital bagi Mahasiswa Administrasi Pendidikan FIP UPI : Strategies for Strengthening Islamic Da’wah in the Digital Space for Students of Educational Administration, FIP UPI - Anyelir Wahyuningtyas; Gita Dwi Rahayu; Airil Hamdani; Zidane Fauzi Ramadhan; Edi Suresman (Litera Academica Publishing, 2026)
The development of information and communication technology has transformed patterns of social interaction, including activities related to Islamic da’wah (religious outreach). Digital spaces such as social media, video platforms, and instant messaging applications have become new mediums for disseminating Islamic values, particularly among university students. However, digital da’wah also faces various challenges, including low levels of digital religious literacy, the spread of religious hoaxes, radical content, and the lack of engaging and educational communication strategies. This study aims to identify the problems of Islamic da’wah in the digital era, analyze the contributing factors, and formulate strategies to strengthen Islamic da’wah in the digital space for students of Educational Administration at FIP UPI. The research employs a descriptive method with a qualitative approach through observation, interviews, and documentation studies. The findings are expected to provide recommendations for effective, adaptive, and relevant digital da’wah strategies aligned with the characteristics of students as digital natives.